Modeling of Clean Water Needs Analysis Based on Dynamic Systems in Lubuk Sikaping District - Suryani, Atma Tri; Mardizal, Jonni (Universitas Negeri Padang, 2024)
Water is the source of life because water is not only needed by humans but also by nature to maintain a stable ecosystem. Humans and other creatures depend on water to grow and develop. The water needs of every livingthing are different and are influenced by the availability of water itself. The utilization of water as a whole in aspects of life becomes more valuable in terms of quantity and quality. The higher the cost of living for each person, the greater the need for water. This study aims to determine the projection of clean water needs in Lubuk Sikaping District from 2023 to 2043 based on population, find out the projection of clean water needs dynamically using powers studio 10 software, and find out whether the availability of clean water is sufficient for the next 20 years. The method used for the planned population projection of the next 20 years uses arithmetic methods. The results obtained in this study the need for clean water increases for the next 20 years, amounting to 125,563 liters/second. The results of water availability in Lubuk Sikaping District are still sufficient for the next 20 years. And based on the same installed capacity each year the availability of water is to be the same or constant every year.